INFORMATION VISIBILITY AND STANDARDIZATION: KEY DRIVERS OF SUPPLY CHAIN RESILIENCE IN INDUSTRY PARTNERSHIPS - Madhusudan Sharma Vadigicherla (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article examines the critical role of collaborative approaches in enhancing supply chain resilience, focusing on a case study of a major initiative in production forecast visibility implementation. The article investigates how shared information systems and standardized processes improve risk management and overall supply chain performance. Through an in-depth analysis of a global manufacturing company's efforts to provide comprehensive production forecasts to plants and suppliers, we explore the impacts on mid to long-term capacity planning, material procurement for long lead-time components, and lead time reduction. The article highlights the importance of standardizing calendars, forecast generation timing, and establishing global visibility to enable effective capacity and material planning. Furthermore, it demonstrates how implementing production forecast accuracy metrics can serve as a baseline for continuous improvement. Our findings suggest that collaborative forecasting enhances supply chain visibility and significantly improves partners' ability to manage risks and respond to disruptions. This article contributes to the growing body of literature on supply chain resilience by providing empirical evidence of the benefits of collaborative approaches and offering practical insights for supply chain managers seeking to improve their organizations' resilience through partnership strategies.